Shp1 in Solid Cancers and Their Therapy - Varone, Alessia; Spano, Daniela; Corda, Daniela (Frontiers in Oncology, 2020)
Shp1 is a cytosolic tyrosine phosphatase that regulates a broad spectrum of biological functions, modulating the flow of information from plasma membrane receptors to nuclear transcription factors. While initially studied in the hematopoietic system, research conducted over the past 10 years has expanded our understanding of the biological role of Shp1 to other tissues, proposing it as a novel tumor suppressor gene functionally involved in different hallmarks of cancer. The main mechanism by which Shp1 curbs cancer development and progression is the ability to attenuate and/or terminate signaling pathways controlling cell proliferation, survival, migration and invasion. Thus, alterations in Shp1 function or expression can contribute to several human diseases, particularly cancer. In cancer cells, Shp1 activity can indeed be affected by mutations or epigenetic silencing that cause failure of Shp1-mediated homeostatic maintenance. This review will discuss the current knowledge of the cellular functions controlled by Shp1 in non-hematopoietic tissues and solid tumors, the mechanisms that regulate Shp1 expression, the role of its mutation/expression status in cancer and its value as potential target for cancer treatment. In addition, we report information gathered from the public available data from The Cancer Genome Atlas (TCGA) database on Shp1 genomic alterations and correlation with survival in solid cancers patients.